Assessment of Knowledge, Perception, and Attitude of Health Cadres Toward Zoonotic Diseases in Rural Area, Malang Regency - Milanitalia Gadys Rosandy; Didi Candradikusuma; Dewi Indiastari; Niniek Budiarti; Heri Sutanto; Sinta Silvia (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2025)
Background: Zoonotic diseases are infections transmitted between animals and humans. Human life is closely intertwined with animals, as many people live alongside animals, consume animal meat, and so forth, which increases their exposure to zoonotic infections. Objectives: This study aims to assess the level of knowledge, perception, and attitude of health cadres toward zoonotic diseases in rural area of Malang Regency. Methods: This study used a cross-sectional approach with a sample size of 108 selected using simple random sampling in rural area of Malang Regency. Data were collected through a questionnaire, including respondent characteristics as well as predisposing, knowledge, perception, and attitude factors for zoonotic diseases. Data were analyzed using a chi-square test for bivariate analysis and a logistic regression test for multivariate analysis. Results: The average age of respondents was 48.1±14,3 years the majority graduating from elementary school (47.2%) and working as farmers (63.9%). The average knowledge score on zoonotic diseases was 8.0 ± 3.9, with 63.9% of respondents scoring below average. The average perception score was 13.4 ± 1.8, with 44.4% of respondents scoring below average. Additionally, 63.9% of respondents had below-average attitude scores (17.3±2,2). The level of education and occupation had a significant relationship with the level of knowledge, perception, and attitude of respondents. Conclusions: The results indicate that the knowledge, perceptions, and attitudes of respondents toward zoonotic diseases are still insufficient. There is a need for enhanced education in this disease to improve public understanding and facilitate early detection.